(untitled) (Journal of Economic Research & Business Administration, 2015)
Agriculture is a very significant industry in the economy of Kazakhstan, in this regard, the industry is strategically important area of public policy. The first state agrarian policy provides a crucial role on the fate of the Kazakh people, its formation and entry into the world sobschestvo indigenous inhabitants of the republic. State to provide the level of economic development of the local population, ancestral traditions – crops and livestock, the overall development of agro should provide an advantage compared to other sectors of the economy. The level of development of agriculture determines the economic security of the country. Kazakhstan having agricultural land in the global market has all the features of the development of competitive agricultural sector. The purpose of this study is to determine the effectiveness of the measures directed by the government to support the development of this industry. As a result, determining the effectiveness of government measures considered agrarian sphere Almaty region of Kazakhstan and the problems of the funds allocated by the JSC «KazAgro»